Deciphering methanolysis of Calophyllum inophyllum oil into biodiesel using KOH-doped Aegle marmelos biochar catalyst: Thermo-kinetics, optimization and cost analysis - Bisheswar Karmakar; Gopinath Halder (Cleaner Chemical Engineering)
The current study presents the catalysed conversion of Calophyllum inophyllum oil with methanol into biodiesel using a single stage approach. Here, the catalyst development essentially valorises waste Aegle marmelos fruit shell through carbonization and subsequent doping with KOH. An indigenously developed heterogeneous catalyst was obtained that can be easily recovered and reused multiple times, proving to be cost efficient according to calculated estimates. This also reduces fuel synthesis costs owing to drastic reduction in wastewater generation. The reaction is optimized through central composite design (CCD) using five process parameters viz. reaction temperature, duration, catalyst concentration, methanol concentration and agitation speed, which resulted in maximum fuel yield of 95.77 %. Conversion of oil was optimal using methanol at 40 %w/w concentration at 60 °C reaction temperature, when the reaction occurs for a duration of 150 min with KOH-doped catalyst at 4 %w/w concentration, requiring a high agitation speed of 850 rpm. From analysis of variance (ANOVA) studies it is clear that the developed model is consistent and statistically relevant. From kinetic and thermodynamic studies, it is seen that the base catalysed transesterification has an activation energy (Ea) = 98.895 kJ/mol and frequency factor (A) = 90.74 min-1, as the reaction is endothermic since enthalpy change (ΔH) was noted to be 809.64 J, along with an entropy change (ΔS) of -64.59 J/K-mol, showing it to be non-spontaneous as well as increasing order in the system.